Flouting Maxims as a Sense of Humor in Indonesian Speech Acts - Zulfadli A. Aziz; Faisal Mustafa; Putri Nurul A’la (Indonesian Journal of EFL and Linguistics, 2019)
The major objective of this research is to analyze the flouting maxims in one of the Indonesian comedy movies, The Guys. This research is focused on identifying the types of flouting maxims and to seek out the reasons behind those flouting performed by Alfi character in the movie. The data for this qualitative research were collected from the utterances produced by character Alfi containing flouting maxims. They were obtained by watching the movie and transcribing the movie script to ensure that no data were accidentally left out. The data was analyzed by classifying the data into types and reasons of flouting maxims, then the researcher verified all the data to ensure that all the data matched and correctly-translated. The results of this research show that character Alfi performed all types of flouting maxims, i.e. quantity, quality, relevance and manner. Flouting maxim of manner is in the highest occurrence and flouting maxim of relevance is in the lowest occurrence. Whereas the reasons that lead character Alfi to flout the maxims are competitive, convivial, collaborative and conflictive. Concerning the reasons of flouting maxims, collaborative reason is in the highest position, and conflictive reason has the lowest position in its occurrence.